ALOHA From the Edge: Reconciling Three Decades of in Situ Eulerian Observations and Geographic Variability in the North Pacific Subtropical Gyre - Kavanaugh, Maria T.; Church, Matthew J.; Davis, Curtiss O.; Karl, David M.; Letelier, Ricardo M.; Doney, Scott C. (Frontiers in Marine Science, 2018)
Global analyses of satellite-and modeled data suggest decreased phytoplankton abundance and primary productivity in oligotrophic gyres as they expand in response to increased surface temperatures, shoaling of surface mixed layers, and decreased supply of subsurface macronutrients. However, concomitant changes have not been evident in situ at Hawaii Ocean Time-series (HOT) Station ALOHA, suggesting physiological or structural reorganization not observed from space, uncharacterized spatiotemporal variability, or uncorrected sensor drift. To address the spatiotemporal variability hypothesis, we compared interannual patterns of in situ data to gyre geography based on multiple metrics including dynamic topography, satellite surface chlorophyll (chl a), and multivariate seascapes using modelled or satellite data. There was only weak evidence of secular increases in the extent of the subtropical gyre; rather, interannual oscillations were evident in physical, biological, and multivariate biophysical definitions of the gyre. Modelled and satellite-based multivariate seascapes agreed well in terms of expansion (surface area of seascapes) and isolation of Station ALOHA (distance to seascape boundary) resulting in combined data record of nearly three decades. Isolation was associated positively with the North Pacific Gyre Oscillation (NPGO), and negatively with Multivariate ENSO Index (MEI) and Pacific Decadal Oscillation (PDO); the converse was true for the gyre’s expansion. This expansion followed a shoaling and freshening of the surface mixed layer and declines in in situ 14C assimilation rates measured over 12 hours in ambient light suggesting that Station ALOHA may serve as an leading indicator of gyre biogeographic patterns. Lags between geographic indicators and in situ conditions appear to partially explain past observed discrepancies between patterns from satellite remote sensing and those from in situ conditions at Station ALOHA appear to be partially explained by lags between geographic indicators and in situ conditions as well as satellite sensor drift and data record length.